Development Of Prosthethic Hand Hardware And Its Control System - Jali, Mohd Hafiz; Alias , Khamis; Ghazali, Rozaimi; Ahmad Izzuddin, Tarmizi; Jaafar, Hazriq Izzuan (Blue Eyes Intelligence Engineering & Sciences Publication, 2015)
-